2017
DOI: 10.1371/journal.pone.0178682
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MR-angiography for the assessment of aortic aneurysms in an experimental mouse model on a clinical MRI scanner: Comparison with high-frequency ultrasound and histology

Abstract: BackgroundMR-angiography currently represents one of the clinical reference-standards for the assessment of aortic-dimensions. For experimental research in mice, dedicated preclinical high-field MRI scanners are used in most studies. This type of MRI scanner is not available in most institutions. The aim of this study was to evaluate the potential of MR-angiography performed on a clinical MR scanner for the assessment of aortic aneurysms in an experimental mouse model, compared to a preclinical high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Due to the high degree of agreement among observers and methodologies, these approaches are well-suited for multi-observer and longitudinal research. Previous studies have demonstrated a high correlation between the USS three-dimensional lumen volume (3DLV) measurement of the murine aorta and more accurate modalities like CT and MRI, as well as histological examination of aortic aneurysms [ 16 , 27 , 28 ]. This is consistent with our findings, which showed a correlation between USS and μCT for the aortic volume measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high degree of agreement among observers and methodologies, these approaches are well-suited for multi-observer and longitudinal research. Previous studies have demonstrated a high correlation between the USS three-dimensional lumen volume (3DLV) measurement of the murine aorta and more accurate modalities like CT and MRI, as well as histological examination of aortic aneurysms [ 16 , 27 , 28 ]. This is consistent with our findings, which showed a correlation between USS and μCT for the aortic volume measurements.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Furthermore, 3DLV measurement of murine aorta has been demonstrated to highly correlate with more sensitive modalities, such as computer tomography and magnetic resonance imaging, as well as histological assessment of aneurysmal aorta. 8 12 13 Despite these observations, 2D USS assessment of murine aorta remains the dominant strategy. 9 10 The results of our study may help preclinical researcher interpret and compare the results between studies utilizing the two differing measurement techniques.…”
Section: Discussionmentioning
confidence: 99%